2002
DOI: 10.1152/ajplung.00476.2001
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol attenuates hypoxia-induced pulmonary endothelin-1 gene expression

Abstract: Earley, Scott, and Thomas C. Resta. Estradiol attenuates hypoxia-induced pulmonary endothelin-1 gene expression. Am J Physiol Lung Cell Mol Physiol 283: L86-L93, 2002. First published February 8, 2002 10.1152/ajplung.00476.2001.-The ovarian hormone 17␤-estradiol (E 2␤) attenuates chronic hypoxia-induced pulmonary hypertension. We hypothesized that E 2␤ attenuates this response to hypoxia by decreasing pulmonary expression of the vasoactive and mitogenic peptide endothelin-1 (ET-1). To test this hypothesis, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 30 publications
1
72
0
Order By: Relevance
“…In addition, there seems to be a clear relationship between sex hormones and the vasoactive mediator endothelin, which is also important in the pathology of PAH. One study showed that estrogen attenuates hypoxia-induced pulmonary ET-1 gene expression in the lung tissue of adult female rats [12], while another found plasma basal levels of ET-1 increased in human males with low testosterone levels [7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there seems to be a clear relationship between sex hormones and the vasoactive mediator endothelin, which is also important in the pathology of PAH. One study showed that estrogen attenuates hypoxia-induced pulmonary ET-1 gene expression in the lung tissue of adult female rats [12], while another found plasma basal levels of ET-1 increased in human males with low testosterone levels [7].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, estrogen has been shown to downregulate endothelin-1, a potent vasoactive and mitogenic mediator [10]. Estrogen also regulates phosphorylation of proteins in the MAPK and ERK signaling pathways [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role of sex hormones with regards to vasoreactivity of the pulmonary vasculature [7,10]. Both testosterone and estrogen have been shown to acutely affect vasoreactivity in various vascular beds [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estradiol inhibits endothelin synthesis. 45,46 Thus, after menopause, this inhibitory effect would be lost. Endothelin synthesis can be upregulated by Ang II, 47 and ET A receptors have been shown to mediate Ang II hypertension in animal studies.…”
Section: Does Endothelin Play a Role In Postmenopausal Hypertension?mentioning
confidence: 99%